The Behavior of Eurocurrency Returns Across Different Holding Periods and Monetary Regimes - LEWIS, KAREN K. (Journal of Finance, 1990)
ABSTRACT Recent empirical studies of the risk premium across foreign exchange and other asset markets such as equity and longer term bonds have found conflicting evidence about the latent variable model restrictions of the consumption‐based intertemporal capital asset pricing model. While studies using data for holding periods of one month or less generally reject the model, evidence using three‐month holding periods indicates that the model cannot be rejected when including the returns on long relative to short deposit rates. This paper investigates the sources of differences in results using returns on foreign exchange and Eurocurrency deposits at three different maturities.